Novel approach to bilateral biliary drainage: EUS-guided hepaticoduodenodenostomy plus hepaticogastrostomy in malignant hilar biliary obstruction - Hijioka, Susumu; Nagashio, Yoshikuni; Maruki, Yuta; Harai, Shota; Agarie, Daiki; Yamashige, Daiki; Okamoto, Kohei; Yagi, Shin; Fukuda, Soma; Komori, Yasuhiro; Kuwada, Masaru; Saito, Yutaka; Okusaka, Takuji (Endoscopy International Open, 2025)
Biliary drainage for unresectable malignant hilar biliary obstruction (MHBO) can be technically challenging; therefore, there is a requirement for new treatment methods. This study evaluated the efficacy and safety of a novel bilateral drainage method—endoscopic ultrasound-guided hepaticoduodenostomy plus hepaticogastrostomy (EUS-HDGS)—which combines EUS-guided hepaticoduodenostomy (EUS-HDS) and hepaticogastrostomy (EUS-HGS).From 2018 to 2024, we reviewed eight cases of EUS-HDGS from 749 EUS procedures. Both EUS-HDS and EUS-HGS were performed simultaneously. The study outcomes were technical success, clinical success (reduced bilirubin levels or improved cholangitis within 14 days), and adverse events.Technical success was achieved in 87.5% cases (7/8), whereas clinical success was observed in 75.0% (6/8). Mild peritonitis occurred in 25% of patients (2/8) and 75.0% of patients (6/8) experienced recurrent biliary obstruction, with successful reintervention achieved in all cases. Median stent patency period was 90 days (95% confidence interval: 47.0–133).EUS-HDGS is a safe and effective drainage method for treating refractory MHBO and has potential as a viable treatment option.
Keywords: Endoscopic ultrasonography; Biliary tract; Intervention EUS; Pancreatobiliary (ERCP/PTCD); Strictures